2018
DOI: 10.5505/ejm.2018.92053
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Serum CRP Level on Postoperative Atrial Fibrilation Occurrence in Patients who had Coronary Bypass Surgery

Abstract: Coronary artery bypass grafting (CABG) is the most common cardiac operation performed worldwide. We aimed to evaluate the relationship between post-operative serum C-reactive protein (CRP) level and atrial fibrillation (AF) in patients who received CABG. A total of 198 patients who had undergone CABG between January 2016 and February 2018 in our cardiovascular surgery clinics were included in the study. According to CRP levels, patients were into 2 groups; Group 1 serum CRP level <8.0mg/L and Group 2 serum CRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…(2018) in Turkey concluded that inflammatory factors, especially increased CRP levels, were strongly associated with AF in cardiac patients [22]. Therefore, it appears that by following patients with AF and performing serial tests related to inflammatory factors, especially repeated evaluation of CRP levels in these patients, the cause and effect role between inflammatory factors and AF could be reported more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) in Turkey concluded that inflammatory factors, especially increased CRP levels, were strongly associated with AF in cardiac patients [22]. Therefore, it appears that by following patients with AF and performing serial tests related to inflammatory factors, especially repeated evaluation of CRP levels in these patients, the cause and effect role between inflammatory factors and AF could be reported more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) in Turkey concluded that inflammatory factors, especially increased CRP levels, were strongly associated with AF in cardiac patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors may play a role in the development of AF. During and following surgery, many factors such as blood and blood product use (22), infection, advanced age, obesity, low oxygen level, long operation time, prolonged intubation time and elevated C-reactive protein (CRP) have been associated (23). Some studies have suggested that the incidence of atrial fibrillation following cardiac surgery is higher in smokers than in non-smoking patients.…”
Section: Discussionmentioning
confidence: 99%